Administrators’ Administrative Skills Affecting the Knowledge Management in Schools under the Secondary Educational Service Area Office Nakhon Pathom - Aongmanee, Wuttigorn; Phravaddhanavajiramedhi (Journal of Dhamma for Life, 2025)
The purposes of this research were: 1) to study the administrative skills of school administrators under the Secondary Educational Service Area Office Nakhon Pathom, 2) to study knowledge management in schools under the Secondary Educational Service Area Office Nakhon Pathom and, 3) to study the administrative skills of school administrators that affect knowledge management in schools under the Secondary Educational Service Area Office, Nakhon Pathom. The sample group in this research consists of 320 participants, including school directors, heads of four administrative units, and teachers from schools under the Secondary Education Service Area Office Nakhon Pathom, representing 29 schools. The research instrument used in this study was a questionnaire. The data were analyzed using statistical software. The statistical methods used for data analysis include frequency, percentage, mean (𝑥̅), standard deviation (S.D.), and hypothesis testing through stepwise multiple regression analysis. The results of research were found that: 1) The administrative skills of school administrators under the Secondary Educational Service Area Office Nakhon Pathom in overall was at a high level. When considering each aspect, all areas are rated at a high level. The average scores in each area, ranked from highest to lowest, are as follows: conceptual skills, cognitive skills, human skills, technical skills, and educational and teaching skills, respectively. 2) The knowledge management in schools under the Secondary Educational Service Area Office Nakhon Pathom in overall was at a high level. When considering each aspect, all areas are rated at a high level. The average scores in each area, ranked from highest to lowest, are as follows: learning, access to knowledge, sharing and exchanging knowledge, knowledge discovery, organizing knowledge systematically, synthesizing and filtering knowledge, and creating and seeking knowledge, respectively. 3) The administrative skills of school administrators that affect knowledge management in schools under the Secondary Educational Service Area Office Nakhon Pathom, ranked by the prediction coefficient in order of importance, are as follows: human skills, cognitive skills, technical skills, educational and teaching skills, and conceptual skills, respectively. These skills can significantly explain the variance in the administrative skills of school administrators affecting knowledge management in schools under the Secondary Educational Service Area Office Nakhon Pathom was statistical significance at 0.01 level.